Education Materialised Reconstructing Teaching and Learning Contexts through Manuscripts - Brinkmann, Stefanie; Ciotti, Giovanni; Valente, Stefano; Wilden, Eva Maria (Studies in Manuscript Cultures, 2021)
This volume reveals how manuscripts may be used in gaining knowledge of educational practices across Africa, Asia and Europe from the Babylonian period up to the twentieth century. Four major research topics are addressed: transmission of knowledge through institutional or private educational settings, organisation of knowledge as reflected in syllabi, exegetical practices and annotations, adaptation of learning traditions.